2023
DOI: 10.1186/s12894-023-01219-4
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the role of PSMA PET in active surveillance

Abstract: Introduction Accurate grading at the time of diagnosis is fundamental to risk stratification and treatment decision making, particularly for men being considered for Active Surveillance (AS). With the introduction of prostate-specific membrane antigen (PSMA) positron emission tomography (PET) there has been considerable improvement in sensitivity and specificity for the detection and staging of clinically significant prostate cancer. Our study aims to determine the role of PSMA PET/CT in men wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 25 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…After reviewing the titles and abstracts, 1766 of them were excluded for different reasons: 534 because the reported data were not within the field of interest of this review, 126 were systematic reviews, 110 were care series or case reports, 974 were conference abstracts, 12 were editorials, nine were study protocols, and one study had the same cohort as another paper. Consequently, eight studies addressing the role of PSMA PET/CT in the clinical setting of AS were selected and the full texts were retrieved [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. No additional studies were found after analyzing the reference lists of these articles ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After reviewing the titles and abstracts, 1766 of them were excluded for different reasons: 534 because the reported data were not within the field of interest of this review, 126 were systematic reviews, 110 were care series or case reports, 974 were conference abstracts, 12 were editorials, nine were study protocols, and one study had the same cohort as another paper. Consequently, eight studies addressing the role of PSMA PET/CT in the clinical setting of AS were selected and the full texts were retrieved [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. No additional studies were found after analyzing the reference lists of these articles ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the total number of studies included in the systematic review, three were retrospective [ 22 , 23 , 26 ], whereas five had a prospective design [ 20 , 21 , 24 , 25 , 27 ]. In terms of radiopharmaceuticals used, five studies were performed using [ 68 Ga]Ga-PSMA-11 [ 20 , 21 , 23 , 24 , 27 ], a single study with [ 18 F]F-PSMA-1007 [ 22 ], a study with both [ 68 Ga]Ga-PSMA-11 and [ 18 F]F-DCFPyL [ 26 ], while in one study, the tracer used was not specified and referred to as a general [ 68 Ga]Ga-PSMA [ 25 ], although different papers published by the same group used [ 68 Ga]Ga-PSMA-11. Moreover, six studies were performed using a PET/CT tomograph [ 21 , 23 , 24 , 25 , 26 , 27 ] and two studies used PET/MRI [ 20 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations